Global Trends in Local Wisdom-Based School Education: A Comprehensive Bibliometric Review (2009–2025) - Syamsidar Saleng; Ishaq; Eny Syatriana (Journal of Local Wisdom in Education, 2025)
This study presents a comprehensive bibliometric analysis of global and national trends in integrating local wisdom within school education between 2009 and 2025. The integration of local wisdom into formal education is gaining urgency amid global calls for culturally responsive, sustainable, and identity-based learning. Despite growing scholarly interest, no prior study has systematically mapped the evolution of this research field. Addressing this gap, the study analyzed 391 Scopus-indexed documents, including journal articles, conference papers, and book chapters, using VOSviewer and Biblioshiny to examine publication trends, key authors, influential institutions, geographic distribution, core sources, and thematic keyword clusters. Results indicate a sharp increase in publications from 2016 onward, with Indonesia emerging as the dominant contributor. Key thematic areas include character education, technological integration, multicultural pedagogy, and ecological literacy. The novel contributions of this study lie in its quantitative, data-driven perspective, which complements previous qualitative findings and offers a macro-level understanding of research trajectories and intellectual structures. The study concludes that local wisdom-based education is becoming a critical domain within educational research, particularly in Southeast Asia, and calls for expanded international collaboration and methodological innovation. By systematically mapping this field, the study contributes to advancing culturally grounded educational practices. It provides actionable insights for educators, policymakers, and researchers seeking to enhance the relevance and inclusivity of education systems.